Evolution of weak discontinuities in a non-ideal radiating gas - Singh L.P.; Husain A.; Singh M. (My University, 2025)
A method of wavefront analysis is used to study the formation of shock waves in a two-dimensional steady supersonic flow of a non-ideal radiating gas past plane and axisymmetric bodies. The gas is taken to be sufficiently hot for the effect of thermal radiation to be significant, which is, of course, treated by the optically thin approximation to the radiative transfer equation. Transport equations, which lead to the determination of the shock formation distance and also to conditions which insure that no shock will ever evolve on the wavefront, is derived. The influence of the parameter of the non-idealness, upstream flow Mach number in the presence of thermal radiation on the behavior of the wavefront are examined. © 2010 Elsevier B.V.